IMPLEMENTATION OF THE PROSPEROUS AFRICA PROGRAM UNITED STATES GOVERNMENT FOREIGN ASSISTANCE IN AFRICA - Tasya Mysheta; Andi Kurniawan; Garcia Krisnando Nathanael (POLITICO, 2022)
This study aims to examine Implementation Of The Prosperous Africa Program United States Government  Foreign Assistance In Africa. The interests of the United States Government to maintain security and prosperity is a priority that is carried out by America. Africa is one of the continents that has received more attention from the United States in recent decades, with potential starting to show in Africa and American interests, hence the Prosperous Africa Initiative program created during the Trump administration. However, due to the lack of research examining Prosperous Africa, this research is expected to be a reference for studying the implementation of development assistance points. Conceptually, foreign aid is provided by developed countries to assist development in developing countries, but of course it is also motivated by their interests. In this case, two African countries are used as case studies, namely Nigeria and Kenya. This program has increased the added value of the agribusiness sector, especially the tomato processing industry. In Kenya Prosper Africa has helped improve technological capabilities in the agricultural sector, especially irrigation systems. This program is a manifestation of the interests of the United States Government to balance China's influence on the African continent. A good agricultural sector will create great agribusiness sector opportunities, Prosperous Africa sees such opportunities in Nigeria and Kenya, with the strength of the American Government through technology for agriculture being an opportunity for American companies and the private sector to take advantage of.Keywords: Implementation; Prosperous Africa Program; Foreign; Government